2020
DOI: 10.2147/jir.s284090
|View full text |Cite
|
Sign up to set email alerts
|

<p>Lymphatic Flow: A Potential Target in Sepsis-Associated Acute Lung Injury</p>

Abstract: Sepsis is life-threatening organ dysfunction caused by an imbalance in the body's response to infection and acute lung injury (ALI) related to sepsis is a common complication. The rapid morbidity and high mortality associated with sepsis is a significant clinical problem facing critical care medicine. Inflammation plays a vital role in the occurrence of sepsis. Notably, the body produces different immune cells and pro-inflammatory factors to clear pathogens. However, excessive inflammation can damage multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…In addition, researchers reported that there was a relationship between TRSF and MDD/suicide, 19 and TRSF might have a role in inflammation mechanism. 32 , 33 Here, the significantly decreased TRSF level was found in MDD patients with SI. The abovementioned findings suggested that inflammatory response might be essential in the occurrence of SI in MDD patients.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, researchers reported that there was a relationship between TRSF and MDD/suicide, 19 and TRSF might have a role in inflammation mechanism. 32 , 33 Here, the significantly decreased TRSF level was found in MDD patients with SI. The abovementioned findings suggested that inflammatory response might be essential in the occurrence of SI in MDD patients.…”
Section: Discussionmentioning
confidence: 51%
“…This could explain the slow repair of organ function. In this context, the mechanism directly responsible for the beneficial effect of hyperthermia may also be the repair of lymphatic drainage in inflamed tissue (3, 4).…”
Section: To the Editormentioning
confidence: 99%
“…Damage of lymphatic vessels by infection with SARS-CoV-2 is likely because the endothelia express the ACE2 receptor [ 65 ]. In addition, the glycocalyx of lymphatic endothelia is similar to endothelia of blood vessels and may allow attachment of the virus [ 66 ]. Since the lymphatics also have a role in the immune system, the authors of that study hypothesized that the phenomenon of the cytokine storm may be caused by disorder of lymphatic flow.…”
Section: Lung Changes In Ardsmentioning
confidence: 99%
“…The larger collecting lymphatics possess valves at regular intervals to prevent retrograde backflow and smooth muscles, and are capable to perform contractions. By contrast, pulmonary pre-collecting and collecting lymphatics have valves but lack smooth muscle cells [ 66 ].…”
Section: Lung Changes In Ardsmentioning
confidence: 99%